Effect of integrated nutrient management on growth and yield of spring onion (Allium fistulosum var. Chiru Maroi) - HENARITA, H; ANAL, P S M; DEVI, A K B; SINGH, S R; SINGH, N O (The Indian Journal of Agricultural Sciences, 2026)
The experiment, conducted during rainy (kharif) season (July–November) of 2022 at College of Agriculture, Central Agricultural University, Imphal, Manipur, concluded that the application of 100% recommended dose of fertilisers (RDF) combined with 2.5 t/ha vermicompost (T8), as well as 100% RDF + 10 t/ha FYM (T2), proved to be the most effective treatments for achieving optimum growth and yield of local spring onion. These integrated nutrient management practices enhanced vegetative growth, yield attributes, and overall productivity. For future research, studies may be undertaken to evaluate the effects of different doses and combinations of organic manures such as bio-fertilisers, vermicompost, poultry manure, and others alongside chemical fertilisers on the growth, yield, and quality of spring onion. Additionally, further investigations into optimum spacing and planting dates may provide valuable insights into maximising yield potential and improving bulb quality under varying agro-climatic conditions.